Using artificial intelligence to examine online patient reviews. (November 2021) - Ferguson, Sarah Lord; Pitt, Christine; Pitt, Leyland
Healthcare consumers are increasingly turning to online sources such as educational websites, forums and social media platforms to share their experiences with medical services and to demystify the uncertainties associated with undergoing various procedures. This study demonstrates a non-invasive way of understanding the feelings and emotions that consumers share via electronic word of mouth. By using IBM Watson, a content analysis tool that harnesses artificial intelligence, we show how a large amount of unstructured qualitative data can be transformed into quantitative data that can be subsequently analysed to generate novel insights into what patients are sharing about their healthcare experiences online.